Preventing deaths due to the hypertensive disorders of pregnancy - von Dadelszen, Peter; Magee, Laura A. (Best practice & research. Clinical obstetrics & gynaecology, 2016)
In this chapter, taking a life cycle and both civil society and medically oriented approach, we will discuss the contribution of the hypertensive disorders of pregnancy (HDPs) to maternal, perinatal and newborn mortality and morbidity. Here we review various interventions and approaches to preventing deaths due to HDPs and discuss effectiveness, resource needs and long-term sustainability of the different approaches. Societal approaches, addressing sustainable development goals (SDGs) 2.2 (malnutrition), 3.7 (access to sexual and reproductive care), 3.8 (universal health coverage) and 3c (health workforce strengthening), are required to achieve SDGs 3.1 (maternal survival), 3.2 (perinatal survival) and 3.4 (reduced impact of non-communicable diseases (NCDs)). Medical solutions require greater clarity around the classification of the HDPs, increased frequency of effective antenatal visits, mandatory responses to the HDPs when encountered, prompt provision of life-saving interventions and sustained surveillance for NCD risk for women with a history of the HDPs. •The contribution of pregnancy hypertension to maternal mortality is almost certainly under-estimated.•Solutions relate to both societal and medical interventions.•Improving the health, dietary and self-efficacy status of girls and adolescent women will reduce the health and societal impacts of pregnancy hypertension and its long-term health sequelae.•The provision of effective, appropriately-resourced, and respectful maternity services will reduce the burden of adverse maternal and perinatal outcomes related to pregnancy hypertension.•Appropriate interventions will reduce both the personal (for women) and inter-generational (for their children) impact of pregnancy hypertension on non-communicable disease risks and adverse outcomes.